Frontiers in pediatric testicular torsion: An integrated review of prevailing trends and management outcomes. Issue 5 (October 2018) - Osumah, T.S.; Jimbo, M.; Granberg, C.F.; Gargollo, P.C.
Summary: Testicular torsion remains the most frequent cause of testicular ischemia, especially in adolescents and young adults. Timely diagnosis and intervention are keys to saving the affected testicle. This review presents current trends in the diagnosis and treatment of torsion, potential pitfalls and consequent outcomes. Additionally, other salient issues surrounding testicular torsion are also discussed, including: pathogenesis of injury, legal ramifications, fertility outcomes, novel management techniques, and recent advances in diagnostic technology.